(untitled) (Acta Scientiarum. Health Sciences, 2014)
Hundreds of children and young people die from fatal accidents or violence every year and others suffer the consequences of non-lethal lesions. Knowing the associated factors is essential for moving forward in the control of these events. The study analysed the families’ perception and factors associated with deaths due to external causes of children, adolescents and young people. Cross-sectional study from deaths from accidents and violence in the age group of 0 to 24 years in the city ofCuiabá-State of Mato Grosso, followed by a domestic survey with the families. The families could not tell whether the accident/violence was a foreseeable event and do not believe that habits/lifestyle have favoured the occurrence. Intentional deaths showed a greater association with factors: maternity/paternity in adolescence, role overload of the mother, consumption of alcohol/drugs, family conflicts and prior deaths from external cause. Feelings of appreciation (study, housing, work, and whether the victim’s pregnancy has been desired) were positive in a higher proportion among cases at which the victims died in an accident. The families had easy access to health care services; however, it was difficult to access the network of social and religious support. Associated factors differ according to the intentionality of the event.